Dissolved iron analysis in estuarine and coastal waters by using a modified adsorptive stripping chronopotentiometric (SCP) method - Riso, R.; Pernet-Coudrier, B.; Waeles, M.; Le Corre, P. (Analytica Chimica Acta, 2007)
An electrochemical method based on adsorptive stripping chronopotentiometry (SCP) with a rotating mercury film electrode has been developed for the determination of dissolved iron (III) at subnanomolar concentrations in estuarine and coastal waters. The detection limit was 0.11 nM after adsorption time of 60 s. Compared to the other chronopotentiometric methods available for dissolved iron measurement in natural and estuarine waters, the procedure described here exhibits a 15-fold better sensitivity. Therefore, it allows one to accurately quantify concentrations commonly found in estuarine and coastal waters. Moreover, by using the speciation scheme proposed by Aldrich and van den Berg (Electroanalysis 10 (1998) 369), several forms could be measured, i.e. reactive iron (Fe R) and reactive iron (III) (FeIII R), or estimated, i.e. complexed iron (Fe C) and reactive iron (II) (FeII R). The method described here is reliable, fast, inexpensive and compact. It was applied successfully to the study of the chemical speciation of dissolved iron along the salinity gradient of the Aulne estuary (Brittany-France).